Brain and Optic Chiasm Herniation into Sella after Pituitary Tumor Apoplexy - Pineyro, Maria M.; Furtenbach, Patricia; Lima, Ramiro; Wajskopf, Saul; Sgarbi, Nicolas; Pisabarro, Raul (Frontiers in Endocrinology, 2017)
Brain and optic chiasm herniation have been rarely reported following dopamine agonist treatment for large prolactinomas. We report a case of brain and optical chiasm herniation, secondary to an empty sella due to apoplexy of a prolactinoma and we focus on the specific presentation of this case. A 32-year-old female presented to a neurologist complaining of headaches. Her past medical history was significant for acute vision loss in both eyes accompanied by right 3rd nerve palsy when she was 16 years old. She does not recall any endocrine or imaging evaluation at that time and she had spontaneous partial recovery of left eye vision within 3 months, with permanent blindness of right eye. She did not return to any follow-up until her neurologist consultation. Brain magnetic resonance imaging (MRI) revealed herniation of frontal lobe and optic chiasm into the pituitary sella, as well as a pituitary hypointense lesion measuring 5x5 mm after gadolinium injection. Prolactin levels were 206 ng/ml (4.79-23.3 ng/ml). Repeated prolactin was 258 ng/ml (4.79-23.3 ng/ml). She was started on bromocriptine 2.5 mg/day. Prolactin levels and menstrual cycles normalized. A repeat brain MRI performed 5 months later showed disappearance of pituitary mass, with no changes in brain and chiasmal herniation. To our knowledge, this is the first reported case of brain associated with chiasm herniation secondary to pituitary apoplexy of a prolactinoma. In conclusion, this case highlights that frontal lobe herniation in combination with optic chiasm herniation can be a complication of pituitary tumor apoplexy. Long-term surveillance of patients with pituitary apoplexy is warranted to detect delayed complications.